Changing Antimicrobial Resistance and Epidemiology of Non-Typhoidal Salmonella Infection in Taiwanese Children - Chang, Yi-Jung; Chen, Yi-Ching; Chen, Nai-Wen; Hsu, Ying-Jie; Chu, Hsiao-Han; Chen, Chyi-Liang; Chiu, Cheng-Hsun (Frontiers in Microbiology, 2021)
Nontyphoidal Salmonella (NTS) typically causes self-limiting diarrheal disease but may occasionally lead to invasive infection. This study investigated the epidemiology and antimicrobial resistance of children with NTS infection between 2012 and 2019. We retrospectively analyzed pediatric patients with NTS infections, confirmed by positive cultures, in a tertiary medical center in Taiwan in 2012 and 2019. Clinical features and laboratory data of the patients were collected. Changes in the serogroup category and antimicrobial resistance were also analyzed. Of the total 797 isolates collected, 55 had NTS bacteremia. Compared with the resistance rates in 2012, the rates of resistance to third-generation cephalosporin and ciprofloxacin were significantly higher in 2019 (4.1% vs. 14.3%, P < 0.001; 1.9% vs. 28.6%, P < 0.001), especially in groups B, D, and E. Moreover, we observed significantly higher antimicrobial resistance (25.3%) to third-generation cephalosporin, and approximately half the NTS isolates in the infant group were multidrug-resistant—a higher rate than those of other age groups in 2019. Invasive NTS often presented with a longer fever duration, lower hemoglobin level, and no elevated C-reactive protein (P < 0.05). Noninvasive NTS isolates in 2019 were significantly more resistant to ceftriaxone (P < 0.001) and ciprofloxacin (P < 0.001) than those in 2012. The antimicrobial resistance of NTS in children has increased progressively in the past decade, and different serogroups exhibited different resistance patterns. During this period, infants showed the highest risk to get a third-generation cephalosporin-resistant NTS infection. The high rates of antimicrobial resistance among children with NTS in Taiwan merit continual surveillance.